2013
DOI: 10.1177/1753193413505407
|View full text |Cite
|
Sign up to set email alerts
|

Unifying model of carpal mechanics based on computationally derived isometric constraints and rules-based motion – the stable central column theory

Abstract: This study was part of a larger project to develop a (kinetic) theory of carpal motion based on computationally derived isometric constraints. Three-dimensional models were created from computed tomography scans of the wrists of ten normal subjects and carpal spatial relationships at physiological motion extremes were assessed. Specific points on the surface of the various carpal bones and the radius that remained isometric through range of movement were identified. Analysis of the isometric constraints and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…The row theory described the kinematics of the wrist with two rows organized proximally (lunate and triquetrum) and distally (hamate, capitate, trapezoid, and trapezium), having the scaphoid as a bridge or connection between these two rows. Our mathematical model confirmed that the hamate‐capitate‐trapezoid‐trapezium complex moves relatively rigidly (within 3°), similar to the row theory and previous studies; however, our model demonstrated more variability of motion among the bones of the proximal row. Thus, to consider the bones of the proximal row as part of a rigid element would not be an accurate interpretation of this dataset.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The row theory described the kinematics of the wrist with two rows organized proximally (lunate and triquetrum) and distally (hamate, capitate, trapezoid, and trapezium), having the scaphoid as a bridge or connection between these two rows. Our mathematical model confirmed that the hamate‐capitate‐trapezoid‐trapezium complex moves relatively rigidly (within 3°), similar to the row theory and previous studies; however, our model demonstrated more variability of motion among the bones of the proximal row. Thus, to consider the bones of the proximal row as part of a rigid element would not be an accurate interpretation of this dataset.…”
Section: Discussionsupporting
confidence: 89%
“…Due to the variations in motion patterns of the carpal bone articulations among wrists and lack of large sample sizes, none of these models have been rigorously evaluated for predictive ability. Recently, a stable central column theory of carpal bones was proposed by modeling the isometry of ligament lengths on an in vivo dataset, however, the study was limited to a single specific task (in RU direction) with a small sample size (10 wrists). Computational modeling and finite element analysis are powerful tools for evaluating wrist contact forces in mostly static postures, however, to date, they have not been used for kinematic analysis and prediction.…”
mentioning
confidence: 99%
“…Computer-assisted modeling techniques, specifically, finite element analyses of carpal joint interrelationships, 21 is a promising area of research that can provide a more sophisticated picture of these complex relationships. These techniques can also be used to test the kinematic effects of creating both subtle and gross alterations of normal ligamentous anatomy.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Moreover, we calculated the distance between the tubercle of trapezium and pisiform to quantify the movement of trapezium, selected since previous reports showed that trapezium moves as a single entity with trapezoid, capitate, and hamate. 13,14 Although it was more obvious to the naked eye, there was only a small reduction in the distance measured (28-27 mm). This may Fig.…”
Section: Validation Of 4d Printingmentioning
confidence: 97%